1992
DOI: 10.1093/bja/69.1.51
|View full text |Cite
|
Sign up to set email alerts
|

Acid-Base Management During Hypothermic Cardiopulmonary Bypass Does Not Affect Cerebral Metabolism but Does Affect Blood Flow and Neurological Outcome

Abstract: In order to compare the effects of blood-gas management on cerebral blood flow, metabolism and neurological outcome after hypothermic cardiopulmonary bypass (CPB) we have studied 65 patients undergoing aorto-coronary bypass surgery allocated randomly to either a pH-stat (temperature-corrected blood-gas management) or an alpha-stat (temperature-uncorrected blood-gas management) group. All patients were examined neurologically on the day before and the 7th day after operation. In 20 patients of the pH-stat group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
44
0
1

Year Published

2000
2000
2010
2010

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(52 citation statements)
references
References 25 publications
3
44
0
1
Order By: Relevance
“…They found that an increase in arterial PaCO 2 is associated with a decrease in SVR and a concomitant (12,13,21,22). The results of our study are quite comparable with that of AJston and colleagues (13) wherein no significant changes in SVR could be observed when the two groups of patients undergoing either a stat' or 'pH stat' management were compared; however, in both groups of patients SVR increased with duration of CPB.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…They found that an increase in arterial PaCO 2 is associated with a decrease in SVR and a concomitant (12,13,21,22). The results of our study are quite comparable with that of AJston and colleagues (13) wherein no significant changes in SVR could be observed when the two groups of patients undergoing either a stat' or 'pH stat' management were compared; however, in both groups of patients SVR increased with duration of CPB.…”
Section: Discussionsupporting
confidence: 88%
“…Despite numerous studies on the effects of acid base management on organ blood flow, little information is available on the effects of cr stat' versus 'pH stat' management on systemic haemodynamics (5,12). This study demonstrates that there is no difference in systemic vascular resistance in patients undergoing hypothermic CPB under either ct stat' or 'pH stat' conditions.…”
Section: Discussionmentioning
confidence: 70%
“…Newborns, young animals, and adults exhibit similar variations. Interestingly, the strategy of acid-base management has no significant effect on the hypothermic decrease in CMRO 2 [piglet (Aoki et al, 1993;Cheng et al, 1995), rabbit (Hindman et al, 1993), and man (Murkin et al, 1987;Stephan et al, 1992)]. An exception is the study by Skaryak et al (1995) in piglets that found a somewhat lower metabolic rate for oxygen with pH-stat as compared with ␣-stat management.…”
Section: Effect Of Temperature On Cerebral Atp Production and Cerebramentioning
confidence: 99%
“…A majority have reported a hypothermia-induced decrease in CBF, 11,12 whereas others observed unchanged or even increased CBF, 2,13 especially during pH-stat management. 14 Furthermore, whether anesthesia and hypothermia interfere with the CBF-CGU coupling remains to be determined. In clinical studies of patients undergoing cardiopulmonary bypass, an unchanged or increased mean CBF associated with a markedly decreased mean CGU ("hyperperfusion") has been interpreted as uncoupling of CBF from metabolism.…”
Section: See Editorial Comment Page 1401mentioning
confidence: 99%